2021
DOI: 10.1111/aphw.12281
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and stress in times of the COVID‐19 pandemic: The role of personal resources

Abstract: There is still little research on the association between COVID‐19‐related stress and insufficient sleep. As distress is assumed to be high in these times, the role of personal resources becomes more important. The current study aimed to investigate the predictive role of COVID‐19‐related stress, positive affect, and self‐care behavior for subjective sleep quality and sleep change measures since the outbreak of COVID‐19 in Germany. A sample of 991 adults ( M = 34.11 years; SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
(60 reference statements)
0
25
1
Order By: Relevance
“…Heightened levels of rumination and suppression have been observed in those exposed to higher levels of pandemic-related stressors, and are associated with higher levels of depression and anxiety symptoms, including in prospective studies ( Low, Overall, Chang, Henderson, & Sibley, 2021 ; Weissman et al, 2021 ; Ye et al, 2020 ; Zhou, MacGeorge, & Myrick, 2020 ). The pandemic has resulted in meaningful changes in sleep quantity and quality, and disruptions in sleep have been linked to higher levels of pandemic-related stress as well as symptoms of depression and anxiety ( Benham, 2021 ; Gupta, Sharma, Kumar, & Mahajan, 2020 ; Merikanto et al, 2021 ; Robillard et al, 2021 ; Stanton et al, 2020 ; Ulrich et al, 2021 ; Werner, Kater, Schlarb, & Lohaus, 2021 ). Although data on reward processing during the pandemic is limited, a prospective study found that blunted pre-pandemic reward processing was associated with greater suicidal ideation during the pandemic ( Hutchinson et al, 2021 ).…”
Section: Stress Mechanismsmentioning
confidence: 99%
“…Heightened levels of rumination and suppression have been observed in those exposed to higher levels of pandemic-related stressors, and are associated with higher levels of depression and anxiety symptoms, including in prospective studies ( Low, Overall, Chang, Henderson, & Sibley, 2021 ; Weissman et al, 2021 ; Ye et al, 2020 ; Zhou, MacGeorge, & Myrick, 2020 ). The pandemic has resulted in meaningful changes in sleep quantity and quality, and disruptions in sleep have been linked to higher levels of pandemic-related stress as well as symptoms of depression and anxiety ( Benham, 2021 ; Gupta, Sharma, Kumar, & Mahajan, 2020 ; Merikanto et al, 2021 ; Robillard et al, 2021 ; Stanton et al, 2020 ; Ulrich et al, 2021 ; Werner, Kater, Schlarb, & Lohaus, 2021 ). Although data on reward processing during the pandemic is limited, a prospective study found that blunted pre-pandemic reward processing was associated with greater suicidal ideation during the pandemic ( Hutchinson et al, 2021 ).…”
Section: Stress Mechanismsmentioning
confidence: 99%
“…Unlike mental health, other clinical issues, such as musculoskeletal injury, were not severely aggravated by lockdowns [ 9 ]. Psychological effects appear to be influenced by sex, with females, in general, demonstrating greater COVID-19-related fear [ 8 ] and stress [ 10 ]. Female athletes also reported greater perceived stress than males during lockdown [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently a paucity of research examining individuals’ overall perceived psychological wellbeing during the COVID-19 pandemic. Measures of wellbeing used in prior research during the pandemic either have tended to model COVID-19-specific stress [ 9 , 10 , 11 , 12 ] instead of wellbeing or have only measured general wellbeing rather than a more comprehensive pandemic-related wellbeing [ 13 , 14 ]. Research demonstrates that restoration of a single area of life disruption, such as daily habits, does not necessarily improve perceived wellbeing [ 15 ].…”
Section: Introductionmentioning
confidence: 99%